Body weight prediction of Brakmas and Bali cattle using body measurements - Mohd. Hafiz, A.W.; Izuan Bahtiar, A.J.; Mohamad Hifzan, R.; Ashraff, A.L.; Ariff, O.M.; Faezal Ashraff, A.L. (Malaysian Journal of Animal Science, 2016)
In the rural areas facilities for farm animal weighing are often difficult to find and the construction of such facilities is relatively expensive. Therefore a study was conducted with the objective to estimate body weight of Brakmas and Bali cattle using prediction equations of linear body measurements. Data of body weight and body measurements, namely withers height, body length and heart girth from 279 heads of Brakmas (age 1 to 10 y old) and 74 heads of Bali (age 1 to 10 y old) cows were collected. The animals were in average body condition of 3 (1= emaciated, 3= moderate fat cover, and 5= excess fat cover). The correlation analysis showed that body weight of Brakmas cattle was highly correlated with its body length, heart girth and withers height with the correlation coefficients of 0.967, 0.964 and 0.942, respectively, while body weight in Bali cattle had the highest correlation with heart girth followed by body length and height at withers with the correlation coefficient of 0.985, 0.954 and 0.945, respectively. Regression analysis showed that body length provided a good estimate of live body weight with high precision as it accounted for 91.6% of the variability in body weight in Brakmas cattle, while heart girth accounted 97.1% of body weight variability in Bali cattle. The combination of body length-withers height, body length-heart girth and body length-withers height-heart girth showed an improvement in terms of predictive precision with the changes of 0.21%, 0.21% and 0.44%, respectively, in coeficient of determination (R2) compared to a single measure of body length in Brakmas cattle. The combination of heart girth-body length did not show any change in R2 in Bali cattle compared to a single measure of heart girth. Combining heart girth-height at withers and the combination of all body measurements showed the increment in coefficients of determination at 0.41% and 0.51%, respectively as compared to heart girth. Although the combination of body measurements showed the highest coefficient of determination, the use of a single measure of body measurement - body length in Brakmas cattle and heart girth in Bali cattle -to predict the body weight is more practical under field condition as they accounted for most of the variability in body weight of Brakmas and Bali cows.